CORE HOUSE DEVELOPMENT AS AN EFFORTS TO INCREASE FEASIBILITY HOUSE IN INDON - Nike Tilamsari Hutoyo; Ardhya Nareswari (Ide dan Dialog Desain Indonesia (Idealog), 2021)
This paper focuses on examining the role of the growing core house concept in increasing the livability of houses and housing in Indonesia. The house is a very valuable place vital for human development, the house is a shelter and a basic human need. Therefore the house must have the feasibility to support all activities of normal daily life. However, the feasibility of houses and housing is still a problem in Indonesia, this is due to the construction of houses and housing that does not really consider functionality but is more profit-oriented. This study uses a literature study research method. The concept of developing core houses to grow can be an alternative to increase the feasibility of houses and housing in Indonesia with several potentials, such as simple design, ease of construction, and affordability and weaknesses, such as being able to create slum areas if not planned properly. Keywords: core house grows, feasibility